Angular Dependence of Coercivity with Temperature in Co-Based Nanowires - Escrig-Murua, J; Espejo-Pina, A (Elsevier, 2015)
The magnetic behavior of arrays of Co and CoFe nanowire arrays has been measured in the temperature range between 100 and 300 K. We have paid particular attention to the angular dependence of magnetic properties on the applied magnetic field orientation. The experimental angular dependence of coercivity has been modeled according to micromagnetic analytical calculations, and we found that the propagation of a transversal domain wall mode gives the best fitting with experimental observations. That reversal mode holds in the whole measuring temperature range, for nanowires with different diameters and crystalline structure. Moreover, the quantitative strength of the magnetocrystalline anisotropy and its magnetization easy axis are determined to depend on the crystalline structure and nanowires diameter. The evolution of the magnetocrystalline anisotropy with temperature for nanowires with different composition gives rise to an opposite evolution of coercivity with increasing temperature: it decreases for CoFe while it increases for Co nanowire arrays. © 2015 Elsevier B.V.All rights reserved.